Análise termo-hidráulico de vaporizadores com tubos horizontais - Landa, Henrique Gerken de (1984)
A new methodology is presented for thermal-fluid dynamic analysis of vaporizers with horizontal tubes using pure substances as process fluid. A computer program has been developed using FORTRAN 77 in order to implement the new method. Several comparisons have been done to show the validity of the proposed methodology with respect to other approaches.